[Translated article] Epidemiologic Profile of the Main Bacterial Sexually Transmitted Infections During the SARS-CoV-2 Pandemic - A. Casanova-Esquembre; B. Fuster Escrivá; J. Lorca Spröhnle; C. Labrandero-Hoyos; R. Peñuelas-Leal; C. Gimeno Cardona; A. Pérez-Ferriols; P. Hernández-Bel (Elsevier, 2023)
Background and objective: The COVID-19 pandemic brought about social changes in 2020 and 2021. The aim of this study was to evaluate the epidemiologic profiles of the main sexually transmitted infections (STIs) of bacterial origin (chlamydia, gonorrhea, and syphilis) diagnosed during this period and compare them to findings from previous years. Material and methods: Drawing on data from Hospital General Universitario in Valencia, Spain, we recorded the number of chlamydia, gonorrhea, and syphilis cases diagnosed monthly by multiplex polymerase chain reaction (PCR) in 2018-2021 and the number of PCR-confirmed SARS-CoV-2 cases diagnosed monthly in 2020-2021. We also collected clinical and demographic information on all patients diagnosed with STIs during the years studied. Results: The total number of STIs diagnosed increased from 570 in 2018-2019 to 664 in 2020-2021. PCR positivity rates were similar in the 2 periods, but the incidence rates were higher during the pandemic. The chronologic correlation between SARS-CoV-2 and STI positivity was negative. Mean age at diagnosis was 29.64 years (95% CI, 19.33-41.14 years) for chlamydia, 30.86 years (95% CI, 20.24-42.45 years) for gonorrhea, and 37.04 years (95% CI, 26.01-51.00 years) for syphilis. The number of men diagnosed with chlamydia increased by 13.85% (95% CI, 6.39-21.08; p = .0003) during the pandemic. Conclusions: We observed a negative correlation between SARS-CoV2 infections and STIs during the pandemic and an increase in chlamydia cases among men. STI cases rose during 2020-2021, indicating that they remain a significant problem that needs to be addressed in young and adult populations. Resumen: Introducción y objetivo: Entre 2020-2021 hemos sufrido una pandemia por el virus SARS-CoV-2. Debido a los cambios sociales por la pandemia, nos hemos propuesto estudiar el comportamiento epidemiológico de las principales infecciones de transmisión sexual (ITS) bacterianas (clamidia, gonorrea y sífilis) durante este periodo y compararlo con periodos previos. Material y métodos: Se recogieron las muestras mensuales de clamidia, gonorrea y sífilis entre los años 2018-2021 y las muestras positivas mensuales de SARS-CoV-2 entre los años 2020-2021 del Hospital General Universitario de Valencia, analizadas por técnica PCR Multiplex. Se recogieron datos clínicos y demográficos de los pacientes con ITS. Resultados: Durante los años 2020-2021 (pandemia) se diagnosticaron más casos de ITS total (664) que durante los años 2018-2019 (prepandemia) (570), con tasas de incidencia superiores y tasas de positividad similares. Se ha observado una correlación cronológica negativa entre las muestras positivas de SARS-CoV-2 y las muestras positivas de ITS. La edad media de los pacientes con diagnóstico de clamidia, gonorrea y sífilis fue de 29,64 (IC 95% 19,33-41,14), 30,86 (IC 95% 20,24-42,45) y 37,04 (IC 95% 26,01-51,00) años, respectivamente. El número de casos de clamidia en varones ha aumentado 13,85% (IC 95% 6,39-21,08; p = 0,0003) en los años de pandemia. Conclusiones: Durante los años de pandemia ha existido una correlación negativa entre los casos de SARS-CoV-2 y los casos de ITS, con más casos de clamidia en varones. Las ITS han aumentado en los dos últimos años, por lo que son un importante problema de salud en la población joven y adulta que merece especial atención.